2023
DOI: 10.1126/sciadv.adi8076
|View full text |Cite
|
Sign up to set email alerts
|

Distinct beta-arrestin coupling and intracellular trafficking of metabotropic glutamate receptor homo- and heterodimers

Joon Lee,
Alberto J. Gonzalez-Hernandez,
Melanie Kristt
et al.

Abstract: The metabotropic glutamate receptors (mGluRs) are family C, dimeric G protein–coupled receptors (GPCRs), which play critical roles in synaptic transmission. Despite an increasing appreciation of the molecular diversity of this family, how distinct mGluR subtypes are regulated remains poorly understood. We reveal that different group II/III mGluR subtypes show markedly different beta-arrestin (β-arr) coupling and endocytic trafficking. While mGluR2 is resistant to internalization and mGluR3 shows transient β-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 98 publications
(163 reference statements)
0
1
0
Order By: Relevance
“…We recently reported that mGluR3, but not mGluR2, couples strongly to β-arrs, dependent on the presence of an S/T-rich region in its CTD 34,60 . Here we show that both CTDs are highly disordered in solution and bind to unilamellar lipid vesicles via their N-terminal regions.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that mGluR3, but not mGluR2, couples strongly to β-arrs, dependent on the presence of an S/T-rich region in its CTD 34,60 . Here we show that both CTDs are highly disordered in solution and bind to unilamellar lipid vesicles via their N-terminal regions.…”
Section: Discussionmentioning
confidence: 99%